To find \(\frac{f(x+h) - f(x)}{h}\) for the function \(f(x) = 32 - 16x\), we follow these steps:
-
Calculate \(f(x+h)\): Substitute \(x + h\) into the function: \[ f(x + h) = 32 - 16(x + h) = 32 - 16x - 16h \]
-
Calculate \(f(x)\): Given \(f(x) = 32 - 16x\).
-
Find \(f(x+h) - f(x)\): Subtract \(f(x)\) from \(f(x+h)\): \[ f(x + h) - f(x) = (32 - 16x - 16h) - (32 - 16x) \] Simplifying this: \[ f(x + h) - f(x) = 32 - 16x - 16h - 32 + 16x = -16h \]
-
Divide by \(h\): Now, we calculate: \[ \frac{f(x+h) - f(x)}{h} = \frac{-16h}{h} = -16 \quad (\text{for } h \neq 0) \]
Thus, the final simplified result is: \[ \frac{f(x+h) - f(x)}{h} = -16 \]